Inventory of Communal Intellectual Property: Among Intellectual Property Right and Cultural Advancement - Kasih, Desak Putu Dewi; Santosa, Anak Agung Gede Duwira Hadi; Dharmawan, Ni Ketut Supasti; Atmaja, I Komang Tri (Faculty of Law, Universitas Pattimura, 2023)
Introduction: This article is to examine the arrangement of the Inventory of Communal Intellectual Property (ICP) in the perspective of the Culture Advancement or IPR and to locate the ideal future concept regarding the Inventory of Communal Intellectual Property (ICP).Purposes of the Research: The purpose of this research is to analyze the Communal Intellectual Property (ICP) inventory concept in the perspective of IPR or Cultural Advancement.Methods of the Research: This research uses normative legal research with the statutory approach and conceptual approach.Results of the Research: In this research was found that the inventory concept in the Cultural Advancement Law is more sustainable rather than Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 13 of 2017, subsequent to the inventory is conducted and it will be continued to the next stage are securing, maintaining, salvaging, and publishing.